2021
DOI: 10.1002/mas.21751
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry studies of nitrene anions

Abstract: Nitrene anions are a class of reactive intermediates that provide a means for studying the corresponding neutral molecules via electron photodetachment spectroscopy and photoelectron spectroscopy. The added electron makes it possible for protected nitrene anions to be manipulated by external electric and magnetic fields of a mass spectrometer. Nitrene anions also display their own unique reactivities as reagents, which have been investigated using ion/molecule reactions. Mass spectrometry of negative ions has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 124 publications
(209 reference statements)
0
1
0
Order By: Relevance
“…Such F‐atom rearrangement from INTI p ‐C 6 H 4 NFSO 2 − (−23.8 kcal/mol) to INT2 p ‐CN‐C 6 H 4 N − SO 2 F (−74.5 kcal/mol) was exothermic. Finally, INT2 p ‐CN‐C 6 H 4 N − SO 2 F dissociated to SO 2 F − at m/z 83 due to the loss of a neutral nitrene p ‐CN‐C 6 H 4 N. However, the calculation results showed that the energy of the triplet‐state nitrene p ‐CN‐C 6 H 4 N is 42.2 kcal/mol less than that of the singlet‐state nitrene p ‐CN‐C 6 H 4 N, indicating that the formation of the triplet‐state nitrene p ‐CN‐C 6 H 4 N is more energetically favorable than that of the singlet‐state nitrene p ‐CN‐C 6 H 4 N 25,26 . Overall, the fragmentation of [ 2 –H] − ( p ‐CN‐C 6 H 4 SO 2 NF − ) to yield the final product ion at m/z 83 and a triplet‐state nitrene p ‐CN‐C 6 H 4 N (−14.7 kcal/mol) was exothermic.…”
Section: Resultsmentioning
confidence: 97%
“…Such F‐atom rearrangement from INTI p ‐C 6 H 4 NFSO 2 − (−23.8 kcal/mol) to INT2 p ‐CN‐C 6 H 4 N − SO 2 F (−74.5 kcal/mol) was exothermic. Finally, INT2 p ‐CN‐C 6 H 4 N − SO 2 F dissociated to SO 2 F − at m/z 83 due to the loss of a neutral nitrene p ‐CN‐C 6 H 4 N. However, the calculation results showed that the energy of the triplet‐state nitrene p ‐CN‐C 6 H 4 N is 42.2 kcal/mol less than that of the singlet‐state nitrene p ‐CN‐C 6 H 4 N, indicating that the formation of the triplet‐state nitrene p ‐CN‐C 6 H 4 N is more energetically favorable than that of the singlet‐state nitrene p ‐CN‐C 6 H 4 N 25,26 . Overall, the fragmentation of [ 2 –H] − ( p ‐CN‐C 6 H 4 SO 2 NF − ) to yield the final product ion at m/z 83 and a triplet‐state nitrene p ‐CN‐C 6 H 4 N (−14.7 kcal/mol) was exothermic.…”
Section: Resultsmentioning
confidence: 97%